Revitalisasi Wayang Beber sebagai Upaya Mempersiapkan Regenerasi Pelukis dan Dalang di Sanggar Naladerma Baluwarti Surakarta - Marwati, Sri; Rosalina , Neni Nurul; Padnobo, Halintar Cakra (Institut Seni Indonesia Surakarta, 2025)
Naladerma Studio as the only place to learn wayang beber in the Surakarta Palace complex is not well managed. The study schedule, teaching materials, modules, members/students, and collections are not well organized. Meanwhile, the existence of Naladerma Studio also supports Surakarta Palace as a center of Javanese traditional culture, although its contribution is not well exposed. Joko Sriyono as the owner of Naladerma Studio has long been known as a Wayang Beber sungging artist and local residents already know him as a wayang beber sungging artist. Joko Sriyono's condition is not like it used to be, due to his increasing age and illness. This has caused his painting activities to be no longer productive and even the 21-meter wayang beber project he designed has not been completed. Currently, there is no longer a successor to manage Naladerma Studio, even though Joko previously founded the studio driven by his concern for the preservation of wayang beber in Solo. Moreover, in the midst of the increasingly modern era. He is worried that in the future the wayang beber culture will be destroyed. Through his studio, Joko can share knowledge about wayang beber to anyone, both visitors and students. For that, there needs to be revitalization to prepare the regeneration of both painters and puppeteers of wayang beber itself as a form and effort to preserve wayang beber so that it does not become extinct. Keywords: revitalization; Wayang Beber, regeneration